Ab initio supported development of TiN/MoN superlattice thin films with improved hardness and toughness. (1st June 2022) - Gao, Zecui; Buchinger, Julian; Koutná, Nikola; Wojcik, Tomasz; Hahn, Rainer; Mayrhofer, Paul Heinz
Abstract: Motivated by density functional theory (DFT)-derived ductility indicators for face centered cubic (fcc, rocksalt) structured TiN/MoN0.5 superlattices and Ti0.5 Mo0.5 N0.75 solid solutions, TiN/MoNy superlattice (SL) thin films with bilayer periods Λ of 2.4, 3.9, 6.6, 9.9, and 23.0 nm and corresponding solid solutions were developed by DC reactive magnetron sputtering. These SLs allow for improved hardness H and critical fracture toughness K IC, with both peaking at the same bilayer period Λ of 9.9 nm (where the MoN0.5 layers crystallize with the ordered β-Mo2 N phase); H = 34.8 ± 1.6 GPa and K IC = 4.1 ± 0.2 MPa√m. The correspondingly prepared fcc-Ti0.5 Mo0.5 N0.77 solid solution has H = 31.4 ± 1.5 GPa and K IC = 3.3 ± 0.2 MPa√m. Thus, especially the fracture toughness shows a significant superlattice effect. This is suggested by DFT—by the increase of the Cauchy pressure from −19 to +20 GPa for the 001-direction (while that in the 100-direction remained high, above 83 GPa) upon increasing Λ from 3 to 4 nm. Together, experimental and computational investigations prove the importance of optimized bilayer periods for highest strength and fracture toughness, as well as optimized N-content for the solid solutions. Graphical abstract: Image, graphical abstract